Marital crises from the point of view of primary school teachers in the state of Laghouat - SENOUCI, Nour el houda; BOUFATEH, Mohamed (Social Sciences Journal, 2023)
The current study aims to identify marital crises from the point of view of the teachers of the primary stage, it was conducted on a sample of (40) teachers who were chosen in an intentional way. The researcher relied on the descriptive approach using the marital crisis detection scale, and statistical methods represented in the peripheral comparison and Cronbach’s alpha to measure the validity and reliability of the scale, as well as the arithmetic mean, the hypothetical mean and the (T) test for significance of differences. After the statistical analysis of the data, we reached the following results The level of couple crises among female teachers at the primary stage is weak due to the variable of age, and there are no statistically significant differences between them due to the variable of housing.